Physiological performance determinants of a 22-km handbiking time trial - Fischer, G.; Figueiredo, P.; Ardigò, L. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate physiological performance determinants of the partial laps and an overall 22-km handbiking (HB) time trial in athletes with high paraplegia. Methods: Seven male HB athletes with spinal cord injury (lesion levels thoracic 2-8) performed a laboratory maximal incremental test under cardiorespiratory-mechanical monitoring including respiratory-exchange ratio (RER), oxygen uptake (VO2), and mechanical power output (PO). Individual first and second ventilatory thresholds (VO2VT1 and VO2VT2), VO2peak, and POpeak were posteriorly identified. Athletes also performed a simulated HB time trial along a 4-lap bike circuit under cardiorespiratory measurement. Overall metabolic cost (C) and %VO2peak (ratio of VO2 to VO2peak) were calculated from race data. Race performance was defined as mean race velocity (v). Results: athletes completed the 22-km HB time trial in 45 ± 6 min, at 29.9 ± 3.6 km/h, with %VO2peak = 0.86 ± 0.10 and RER = 1.07 ± 0.17. VO2peak (r = .89, P = .01), POpeak (r = .85, P = .02), VO2VT1 (r = .96, P = .001), VO2VT2 (r = .92, P = .003), and C (2nd lap, r = .78; 3rd lap, r = .80; and 4th lap, r = .80) were significantly (P < .05) positively correlated with race performance. Within-subjects correlation coefficient revealed a large and significant (r = .68, P < .001) relationship between %VO2peak and v. Conclusions: VO2peak, POpeak, ventilatory thresholds, %VO2peak, and C appeared to be important physiological performance determinants of HB time trial.